Kinesin-1 regulates antigen cross-presentation through the scission of tubulations from early endosomes in dendritic cells - Meriem Belabed (Nature Portfolio, 2020)
Kinesin-1 is a motor protein transporting cargo along microtubules. Here the authors show that kinesin-1 is required for antigen cross-presentation and coordinates endosome scission from early endosomes to allow sorting internalized cargoes towards the recycling endosomal or lysosomal compartments.